2017
DOI: 10.1080/0164212x.2017.1295006
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self-Esteem, General Self-Efficacy, and Approaches to Studying in Occupational Therapy Students: A Cross-Sectional Study

Abstract: The aim of this study was to explore associations between self-esteem, general self-efficacy, and the deep, strategic, and surface approaches to studying. Norwegian occupational therapy students (n = 125) completed questionnaires measuring study approaches, self-esteem, and general self-efficacy. Regression analyses were used to explore the direct relationships between self-esteem, general self-efficacy and the approaches to studying, after controlling for age, gender, prior higher education, and time spent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 59 publications
(71 reference statements)
1
27
1
Order By: Relevance
“…In line with previous findings [37], this study revealed that female students and students who spend more time on independent study were more likely to use strategic approaches to learning. Other studies have also noted that female students appear to be more inclined than male students to use a deep study approach, and less inclined to use a surface approach [12,40,41].…”
Section: Sociodemographic Covariates To Study Approachessupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous findings [37], this study revealed that female students and students who spend more time on independent study were more likely to use strategic approaches to learning. Other studies have also noted that female students appear to be more inclined than male students to use a deep study approach, and less inclined to use a surface approach [12,40,41].…”
Section: Sociodemographic Covariates To Study Approachessupporting
confidence: 92%
“…Diseth's results also showed that "workload" was the only learning environment variable which correlated with examination gradesperceiving the workload to be too heavy had an independent, direct effect on lower examination grades. Conversely, students who have adopted a surface approach to studying with a preference for simple and uncomplicated tasks may have low self-efficacy [37], and may therefore be inclined to perceive the workload as too heavy. For the students in the current sample, mandatory learning activities such as group work and practical skills training, constitute a substantial part.…”
Section: Relationships Between Appropriate Workload and Clear Goals mentioning
confidence: 99%
“…Such research is gaining momentum in related healthcare fields (Mcdonald et al ., ; Reid et al ., ). Future research might also assess study approaches and their development in relationship with the students’ personal characteristics (Bonsaksen, Sadeghi & Thørrisen, ; Prat‐Sala & Redford, ) as well as their perceptions of the learning environment (Fryer & Ginns, ; Kreber, ; Sun & Richardson, ), both of which promising lines of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the detected relationships between productive study approaches and subsequent learning outcomes, researchers have also examined how the presage factors may have an impact on the students' learning process, often conceptualized as their approaches to studying. Among the individual student factors, higher age has been found to be associated with the deep and strategic study approaches [ 11 13 ], whereas the impact of gender has been ambiguous [ 11 ]. Other personal factors, like general self-efficacy [ 13 ] and intrinsic motivation [ 14 ], have also been shown to be associated with productive study approaches among undergraduate students of occupational therapy and psychology, respectively.…”
Section: Introductionmentioning
confidence: 99%